Fuzzy Mathematical Analysis and Advances in Computational Mathematics - Kannan, S. R.; Last, Mark; Hong, Tzung-Pei; Chen, Chun-Hao (Studies in Fuzziness and Soft Computing, 2022)
XIII, 268 p. 101 illus., 49 illus. in color.